An inequality on large deviations - Paulauskas, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Паулаускас. Одно многомерное неравенство для больших уклоненийV. Paulauskas. Apie vieną didelių atsilenkimų nelygybę